ECONOMIC EVALUATION OF FCC FOR WASTEWATER DISCHARGE INTO WATER BODIES RUSSIA AND UZBEKISTAN - , Н. А., О. М. (Municipal economy of cities. Series: «Economy science», 2013)
The problems of the lack of a legal framework for the regulation of water relations in Russia and Uzbekistan. It is shown that the possibility of financing water conservation measures , as a rule , do not allow to reach the values of maximum permissible discharge (MPD ) of pollutants in the required time , it requires either significantly increase funding for environmental activities to the detriment of other areas of economic activity, or reduce the demands on the quality of wastewater discharged into water bodies . These activities are primarily aimed at the implementation of market mechanisms in environmental activities in full.